2014
DOI: 10.1186/1743-422x-11-119
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and phylogenetics of Fennoscandian cowpox virus isolates based on the p4c and atip genes

Abstract: BackgroundCowpox virus (CPXV), a rodent-borne Orthopoxvirus (OPV) that is indigenous to Eurasia can infect humans, cattle, felidae and other animals. Molecular characterization of CPXVs isolated from different geographic locations is important for the understanding of their biology, geographic distribution, classification and evolution. Our aim was to characterize CPXVs isolated from Fennoscandia on the basis of A-type inclusion (ATI) phenotype, restriction fragment length polymorphism (RFLP) profiles of atip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 51 publications
4
15
0
Order By: Relevance
“…1 ) showed the best amplification of fish DNA in reactions using this amount (see below). This is also consistent with other studies using 2 ng of DNA per 20–25 µl PCR reaction, although amplification can be observed at much lower concentrations ( Andrade et al, 2012 ; Jin et al, 2012 ; Bernal-Martínez et al, 2013 ; Batmalle et al, 2014 ; Okeke et al, 2014 ).…”
Section: Methodssupporting
confidence: 92%
“…1 ) showed the best amplification of fish DNA in reactions using this amount (see below). This is also consistent with other studies using 2 ng of DNA per 20–25 µl PCR reaction, although amplification can be observed at much lower concentrations ( Andrade et al, 2012 ; Jin et al, 2012 ; Bernal-Martínez et al, 2013 ; Batmalle et al, 2014 ; Okeke et al, 2014 ).…”
Section: Methodssupporting
confidence: 92%
“…1) showed the best amplification of fish DNA in reactions using this amount (see below). This is also consistent with other studies using 2 ng of DNA per 20-25 µl PCR reaction, although amplification can be observed at much lower concentrations (Andrade et al 2012;Jin et al, 2012;Bernal-Martínez et al, 2013;Batmalle et al, 2014;Okeke et al, 2014) To assess the presence and distribution of the inhibitor various PCR-based experiments were designed. All PCR reactions were developed on 1.0-1.7% agarose gels stained with ethidium bromide and the intensity of the bands obtained was observed under UV light in an ImageQuant 300 (General Electric) gel imaging system.…”
Section: Reviewing Manuscriptsupporting
confidence: 86%
“…Recently, the first poxvirus isolate, CPXV-No-H2, was described that produced V ϩ/ ATI bodies as a stable phenotype (48). Nevertheless, all other CPXVs isolated from Fennoscandia represent the V ϩ ATI phenotype and, hence, encode full-length ati and p4c genes (49). Since RatPox09, unlike FM2292, was isolated from rats and not a reservoir host, it is tempting to speculate that it may have lost the ability to form V ϩ ATIs.…”
Section: Discussionmentioning
confidence: 99%